The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1161/01.cir.61.4.814
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aortic valve replacement in patients with valvular aortic stenosis.

Abstract: Echocardiographic and hemodynamic studies were obtained in 42 consecutive patients undergoing aortic valve replacement for isolated aortic stenosis. Concentric left ventricular (LV) wall thickening, the most common preoperative abnormality, occurred in 95% of patients. LV dilation with reduced fractional shortening was noted in approximately 25% of patients but was severe in only one patient. Six months after operation, LV wall thickness had decreased on average but had not returned to normal and fractional sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(7 citation statements)
references
References 9 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Recent clinical observations of hypertrophy induced by volume (Clark et al, 1980) (Henry et al, 1980) overloads show that only a partial rather than full anatomical regression of ventricular enlargement follows replacement of an abnormal cardiac valve. The functional abnormalities associated with each hemodynamic overload also show only a partial reversal (Kennedy et al, 1977;Pantely et al, 1978).…”
Section: Hypertrophy Reversibilitymentioning
confidence: 99%
“…Recent clinical observations of hypertrophy induced by volume (Clark et al, 1980) (Henry et al, 1980) overloads show that only a partial rather than full anatomical regression of ventricular enlargement follows replacement of an abnormal cardiac valve. The functional abnormalities associated with each hemodynamic overload also show only a partial reversal (Kennedy et al, 1977;Pantely et al, 1978).…”
Section: Hypertrophy Reversibilitymentioning
confidence: 99%
“…'I--3 Aortic valvular stenosis can coexist with various types of subvalvular obstruction.2-14A9 These associated lesions cannot always be demonstrated angiographically, even by left ventriculography in several views. In such cases, obstructive lesions are best diagnosed from pressure gradients detected by catheter pullback from the ventricle to the proximal aorta.2 3, 10, 12, 19 Persistence or recurrence of intraventricular gradients shown by repeated or serial postoperative catheterization signals inadequate resection or regrowth of subvalvular obstructive lesions and possibly the need for further surgical resection.6 [20][21][22][23][24][25] Clinical investigation of normal ejection dynamics has shown that dynamic factors associated with flow contribute to physiologic transvalvular pressure gradients.26 Studies of flow dynamics in hypertrophic cardiomyopathy have cast strong doubt on the premise that large intraventricular pressure gradients are always a consequence of an anatomic obstruction of the outflow tract region.27 Improved instrumentation for measuring pressure28 33 has led to the frequent observation of subvalvular gradients in patients with valvular aortic stenosis without subvalvular pathology in our *The term gradients in this paper is used in the conventional hemodynamic sense, but in fluid dynamic terms represents a driving pressure difference evaluated across a finite distance in the direction of flow. …”
mentioning
confidence: 99%
“…Moreover, when valve replacement is per formed because symptoms have developed, long-term postoperative survival is excellent: in our prospective natural history/prognosis series, survival during an average 4.4 years after operation was 83%. Late postoperative mortality, which was largely related to pros thesis-mediated complications or to coexist ing coronary artery disease, was not predicted by any objective functional characteristic [87]. Therefore, it would appear that symp tom status generally is an excellent indicator as to the appropriate timing of valve replace ment in the patient with aortic stenosis: when valve replacement is undertaken at the time of symptom onset, symptoms almost always are relieved, irreversible left ventricular dys function generally does not occur, and post operative prognosis is excellent.…”
Section: Valvular Heart Diseasementioning
confidence: 83%